The ISO 9001: 2015 Standard and the improvement of processes in the Production Engineering Program of the Centroccidental University Lisandro Alvarado (Venezuela) (Dissertare, 2019)
Every day, organizations cope with great challenges in order to be more competitive, a reality to which the services provided by universities do not escape. That is why one of the competitiveness strategies of these institutions is to establish Quality Management Systems based on the ISO 9001: 2015 international standard. In this descriptive type research, with field design, an evaluation of the processes Internships, Special Degree Work and Community Service belonging to the Production Engineering Program of the Central Western University Lisandro Alvarado is presented, taking as reference the requirements of the ISO 9001: 2015 Standard, for which a checklist based on them was designed and applied. The results obtained showed non-conformance values ​​in relation to said requirements, located at 50%, 41.2% and 29.4% for the aforementioned processes, respectively. Based on these results and as a contribution derived from the study, a guide is presented so that the aforementioned UCLA Production Engineering Program processes have a methodology that allows them to implement a quality management system, based on the ISO 9001: 2015 standard. It is concluded that in a general way, the processes analyzed present aspects of Nonconformity related to resources, people and training, as well as performance evaluation and continuous improvement, so that these processes offer opportunities for improvement under the criteria of the aforesaid rule.
Keywords: ISO 9001 Standard; academic program; quality management system; public university